The mental health effects of the first two months of lockdown and social distancing during the Covid-19 pandemic in the UK - James Banks; Xiaowei Xu (Institute for Fiscal Studies (IFS), 2020)
Mental health in the UK worsened substantially as a result of the Covid-19 pandemic - by 8.1% on average and by much more for young adults and for women which are groups that already had lower levels of mental health before Covid-19. Hence inequalities in mental health have been increased by the pandemic. Even larger average effects are observed for measures of mental health that capture the number problems reported or the fraction of the population reporting any frequent or severe problems, which more than doubled for some groups such as young women. It is important to control for pre-existing recent trends in mental health when attempting to understand and isolate the effects of Covid-19.
Keywords: 330; Psychische Störung; Coronavirus; Soziale Beziehungen; Großbritannien